If America were a village : a book about the people of the United States - Smith, David J. (David Julian), 1944- (Kids Can Press, 2009)
This book uses a simple metaphor to create a snapshot--past, present and future--to help readers imagine America as a village of 100 people, exploring their lives to help children and readers of all ages to discover a whole new vision of America.